Digital Feedback Control of the Flow-Induced Vibrations on the Head Gimbals Assembly in Hard Disk Drives: Design and Implementation - Min, Hequn (2016)
In this paper, a digital feedback control closed-loop is presented for active suppression of flow-induced vibrations on a head gimbals assembly (HGA) in a working hard disk drive (HDD). In this closed loop, a laser Doppler vibrometer was used to detect the flow-induced HGA off-plate vibration as feedback error signals, a digital controller was implemented to filter the feedback signals, and a piezoelectric disk stuck on the HDD cover inner surface was employed to actuate feedback acoustic pressure around the HGA to exert control on the HGA flow-induced vibrations. The digital controller was designed to enable the closed loop with capabilities of single or simultaneous multiple narrowband control on the HGA flow-induced vibrations. Experiments have been carried out for single- or multi-narrowband active suppression of five principal peaks in the HGA off-plate vibration spectrum, around 1256, 1432, 2144, 2524, and 3474 Hz, respectively. Results show that, with the digital closed loop, distinct vibration suppression of up to 15 dB was achieved on those single principal peaks in single-narrowband active controls, or simultaneous distinct suppression of up to 17 dB can be achieved on all those principal peaks in one multi-narrowband active control.